The Effect of Two-Way Conflict on Work Engagement of SPBU PT. Pertamina Retail Ketintang and Jemursari Surabaya - Hadi, Hafid Kholidi (CV ODIS, 2021)
By using the theory of suitability and resource conservation as a theoretical basis, the aim of this study is to propose and test a research model that investigates two-way conflict (work – family conflict and family – work conflict) on work engagement. The data were collected from 60 employees of PT. Pertamina Retail Ketintang and Jemursari Surabaya, Indonesia, in one week apart in two waves which were used to assess the above-mentioned relationship through multiple linear regression on SPSS 23. The results showed that work – family conflict and family – work conflict respectively did not partially affect the work engagement of the employees of the gas station of PT. Pertamina Retail Ketintang and Jemursari Surabaya. In addition, work – family conflict and family – work conflict together (simultaneously) also have no effect on employee work engagement. This study contributes to current knowledge by investigating the interrelationship of two-way conflict in relation to work engagement.